Apps and eHealth interventions for weight management: Hype or hope for childhood obesity prevention - Duarte de Almeida, I. (International Conference on Childhood Obesity, 2017)
The spread of obesity has been declared a worldwide epidemic by the World Health Organization particularly in childhood where overweight and obesity have significant impact on physical health, social and emotional well-being, and self-esteem. Overweight and obese children are likely to stay obese into adulthood and more likely to develop non-communicable diseases like diabetes and cardiovascular diseases at a younger age. This is a serious public and clinical problem since by increasing the risk of many obesity derived health complications, long-lasting treatment for effective results are needed, involving high public and private expenses. There is a limited but growing body of evidence suggesting that mobile eHealth behavioural interventions, such as internet, mobile phone or computer based clinical protocols, may be effective in promoting and sustaining successful weight loss and weight maintenance behaviour changes. Mobile applications (apps) could be an engaging way to involve children in health behaviour changes, capitalizing on portability and affordability of delivering health information via mobile devices and opportunity to use gaming to make health information entertaining. Moreover, eHealth sector interventions, with over 100?000 health apps currently available, could also have an essential role in the development of sustainable systems targeting health costs reducing. Addressing the childhood obesity issues, we study eHealth compliance and eHealth potential to help patients and general practitioners to overcome some of the barriers to managing health risk behaviors. In particular, we discuss (1) the role of eHealth in facilitating routine collection of patient-reported data on lifestyle risk factors, and (2) the role of eHealth in improving clinical management of identified risk factors through provision of tailored feedback, point-of-care reminders, tailored educational materials, and referral to online self-management programs.